2016
DOI: 10.1016/j.surfcoat.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion-fatigue properties of plasma-based low-energy nitrogen ion implanted AISI 304 L austenitic stainless steel in borate buffer solution

Abstract: AISI 304L austenitic stainless steel was modified by using the plasma-based low-energy nitrogen ion implantation (PBLEII) at a process temperature of 400 o C for a processing time of 4 h in order to improve the corrosion-fatigue resistance of the austenitic stainless steel. A single high-nitrogen face-centered-cubic phase ( N) layer with a maximal nitrogen concentration of about 25 at.% was formed on the nitrogen-modified austenitic stainless steel. Compared with the original austenitic stainless steel, the γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Low temperature treatments also allow to increase corrosion-fatigue resistance, due to the improved corrosion resistance. Wang et al [206] tested plasma based low-energy N ion implanted (400 • C, 4 h) AISI 304L with push-pull fatigue experiments in a borate buffer solution at pH 8.4, and they found that corrosion-fatigue strength was about 230 MPa, significantly higher than that of untreated steel (180 MPa). Crack initiation occurred at the interface between the nitrided layer and the matrix, instead of at the surface, as for the untreated alloy.…”
Section: Fatigue Propertiesmentioning
confidence: 99%
“…Low temperature treatments also allow to increase corrosion-fatigue resistance, due to the improved corrosion resistance. Wang et al [206] tested plasma based low-energy N ion implanted (400 • C, 4 h) AISI 304L with push-pull fatigue experiments in a borate buffer solution at pH 8.4, and they found that corrosion-fatigue strength was about 230 MPa, significantly higher than that of untreated steel (180 MPa). Crack initiation occurred at the interface between the nitrided layer and the matrix, instead of at the surface, as for the untreated alloy.…”
Section: Fatigue Propertiesmentioning
confidence: 99%
“…The existed methods to produce nitrogen-containing austenitic steel include high pressure melting and high temperature gas nitriding etc. [5][6][7][8]. Unfortunately, these methods are hard to be carried out in practical applications; especially they are restricted by the demand of special equipments.…”
Section: Introductionmentioning
confidence: 99%
“…These structural steels are being used everywhere in the world for their inherent mechanical properties, but there are problems related to corrosion in aqueous and marine environments. However, the mechanical property and corrosion resistance of AISI 304 austenitic stainless steel (SS304L) has been reported to change with sensitization [1][2][3][4][5][6]. The storage facilities are located in coastal nuclear power plants in the Pacific-rim region, such as in South Korea, Japan, and Taiwan [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The storage facilities are located in coastal nuclear power plants in the Pacific-rim region, such as in South Korea, Japan, and Taiwan [7][8][9]. The implanted nitrogen ions and chromium-base coatings are reported for enhancing the anti-corrosion abilities in solution and in high temperatures [3]. The thermal spray coatings are used for long-term protection on the metal surfaces of structures such as aircrafts, bridges, and wind turbine towers.…”
Section: Introductionmentioning
confidence: 99%